Diketopyrrolopyrrole-based oligomers accessed via sequential CH activated coupling for fullerene-free organic photovoltaics. (November 2016) - Liu, Shi-Yong; Liu, Wen-Qing; Yuan, Cui-Xia; Zhong, Ai-Guo; Han, Deman; Wang, Bo; Shah, Muhammad Naeem; Shi, Min-Min; Chen, Hongzheng
Abstract: Exploring sustainable chemistry for renewable energy plays a key role in meeting the ever increasing energy demand without sacrificing the environment. In this study, two novel diketopyrrolopyrrol(DPP)-based π-conjugated oligomers (named asTPE-DPP 4 andBP-DPP 4 ) have been readily synthesized via a ligand-free Pd-catalyzed sequential activation of CH bond in two steps with good yields starting from simple building blocks. Poly(3-hexylthiophene) is employed as an electron donor to blend with the new DPP-derived electron acceptors for the fullerene-free bulk heterojunction organic photovoltaics. The power conversion efficiency of 2.49% has been achieved, corresponding with an open-circuit voltage of 1.16 V, which is among the highest open-circuit voltages for the single-junction organic photovoltaics. The facilely accessible electron acceptors blended with cost-effective poly(3-hexylthiophene) donor for fullerene-free organic photovoltaics opens a new pathway to access renewable solar energy via sustainable chemistry. Graphical abstract: Highlights: Sequential activation of CH bonds for accessing complicate multi-DPP-based oligomers. The integration of easily accessible acceptors with economical donor for fullerene-free OPVs. High V OC of fullerene-free OPVs using P3HT as donor. Accessing renewable solar energy via sustainable chemistry.